2020
DOI: 10.35848/1882-0786/ab9f62
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature grown single-crystal Si on epi Ge(001)-2 × 1 and its oxidation: electronic structure study via synchrotron radiation photoemission

Abstract: The capped Si expels completely the Ge dimers on top of the epi Ge(001)-2 × 1 and exhibits a multiphase electronic structure consisting of strained surface atoms bonded with Ge in the film. The deposition of molecular oxygen at room temperature removes a portion of the segregated Ge atoms and oxidizes some of the rest. The surface Si atoms exhibit 1+ to 4+ charge states. Heat eliminates the embedded Ge in the capped Si film and transfers the oxygen bonded with the surface Ge to Si. The oxidation reactions occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Compared with the CVD approach, the MBE with a growth temperature of <300 °C yielded less diffusion/segregation of Ge onto epi -Si, which was not observable using the in-situ XPS. Our study of the epi -Si/ epi -Ge using in-situ SRPES showed that the thin epi -Si caused the removal of the Ge–Ge dimers on the top surface of the epi -Ge­(001)-2 × 1; some of the dimers segregated onto the epi -Si surface with the rest diffusing and bonding with Si inside the thin epi -Si film …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared with the CVD approach, the MBE with a growth temperature of <300 °C yielded less diffusion/segregation of Ge onto epi -Si, which was not observable using the in-situ XPS. Our study of the epi -Si/ epi -Ge using in-situ SRPES showed that the thin epi -Si caused the removal of the Ge–Ge dimers on the top surface of the epi -Ge­(001)-2 × 1; some of the dimers segregated onto the epi -Si surface with the rest diffusing and bonding with Si inside the thin epi -Si film …”
Section: Resultsmentioning
confidence: 85%
“…Our study of the epi-Si/epi-Ge using in-situ SRPES showed that the thin epi-Si caused the removal of the Ge−Ge dimers on the top surface of the epi-Ge(001)-2 × 1; some of the dimers segregated onto the epi-Si surface with the rest diffusing and bonding with Si inside the thin epi-Si film. 25 The SRPES results of the single-crystal MBE-Si epitaxially grown on Ge and the SIMS study of the CVD-Si cap on Ge showed that the epi-Si and the Si cap contained diffused Ge atoms. The strained epi-Si should be denoted as Si (diffused Ge) .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Ge segregation in the low temperature (<300 °C) MBE-grown epi- Si on Ge , was below the detection limit of X-ray photoelectron spectroscopy (XPS). We employed the SRPES technique with much higher surface sensitivity and resolution than XPS to study the six MLs thick- epi -Si on epi -Ge­(001).…”
Section: Resultsmentioning
confidence: 98%
“…Fit to the Ge 3d core-level spectra of (a) the pristine epi -Ge­(001)-2×1 . and (b) six MLs of epi -Si on Ge(001), and (c) a fit to the Si 2p core-level spectrum of epi -Si on Ge(001) . [Copyright 2017 & 2020 The Japan Society of Applied Physics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation